Personality Perceived Risk and Travel Intention after The COVID-19 Pandemic: The Case Study in a Bali Resort Village of Canggu - Bei, Theresia Verina Rosari; Suprastayasa, I Gusti Ngurah Agung; Rahjasa, Putu Surya Laksana (Jurnal Kawistara, 2024)
This study aims to determine the influence of human personality and perceived risk on the travel intention of domestic tourists to Canggu, Bali. This research is motivated by the limitations of the previous studies in examining the factors that influence travel intention, especially aspects related to human behavior. This is especially essential for reviving tourism business after the Covid-19 pandemic. This research is based on a survey on domestic tourists who had, are currently, and will be traveling to the resort village of Canggu in Bali. The sample collection method in this study is by using a questionnaire distributed online and offline. The author uses the theory of Hair et al. to determine the minimum number of samples and get 299 respondents in the field. This study uses the Structural Equation Model (SEM) analysis technique to analyze all the data that has been collected. This study found that all major personal characters,namely openness, consciousness, extroversion, agreeableness, and neuroticism, positively affect the intention of visiting domestic tourists to Canggu. In contrast, the perceived risk has a negative effect on the intention of visiting tourists to Canggu. This research encourages managers of tourist destinations in Canggu to consider various personal charaters,perceived risks and travel intentions above in designing marketing strategies and destination development.